The Effect of Mangrove Leaf Extract (Rhizophora apiculata) on Blood Cholesterol Levels of White Mice (Mus musculus) Induced by Egg Yolk - Yuliansyah, Putri Ridha; Nurfadly, Nurfadly; Purwiningsih, Emni; Lubis, Humairah Medina Liza (Universitas Muhammadiyah Sumatera Utara, 2027)
Abstract: Cholesterol is the primary sterol in the human body, produced by the liver. While essential, excessive cholesterol can accumulate as plaques in blood vessels. Rhizophora apiculata contains secondary metabolites such as flavonoids, tannins, alkaloids, saponins, and terpenoids, which are believed to influence HDL and LDL levels. This study aims to investigate the effect of Rhizophora apiculata leaf extract on HDL and LDL levels in male white mice (Mus musculus) induced with egg yolk. This true experimental study applied a post-test with a control group design. A total of 36 white mice were divided into six groups, consisting of negative, positive, and treatment groups. Mice were acclimatised for one week, induced with quail egg yolk, and administered Rhizophora apiculata leaf extract for 30 days. Blood HDL and LDL levels were then measured and analysed using One-way ANOVA. The Shapiro-Wilk and Levene’s tests showed p-values 0.05. The One-way ANOVA indicated significant differences in HDL and LDL levels between groups (p0.05). LSD post hoc tests showed treatment groups P1, P2, and P3 differed significantly from the negative control. Rhizophora apiculata leaf extract affects HDL and LDL levels in male white mice induced by egg yolk.